Exosome-mediated modulation of radioresistance: The radiation-induced bystander effect in prostate cancer cells - Beata Pszczółkowska–Kępa; Wioletta Olejarz; Alicja Głuszko; Grzegorz Wałpuski; Tomasz Lorenc; Beata Brzozowska (PLoS ONE, 2025)
Exosomes are involved in intracellular communication and mediate the radiation-induced bystander effect (RIBE). We assessed the ability of exosomes to modify the radiation response of PC3 and DU145 prostate cancer cells exposed to X-rays. Irradiated cells were analyzed using clonogenic survival and apoptosis assays, while exosome-stimulated cells were evaluated for γH2AX immunostaining, immunoblotting, and apoptosis. Exosomes were isolated via size exclusion chromatography (SEC), characterized by nanoparticle tracking analysis (NTA) and immunoblotting, and ranged from 130 to 137 nm, containing CD63 and CD81. We found that exposure to ionizing radiation (IR) resulted in increased apoptosis and necrosis. To assess exosomes impact on radiation response, exosomes were transferred to non-irradiated and irradiated recipient cells. Non-irradiated PC3 cells stimulated by exosomes released from irradiated PC3 and DU145 cells showed more apoptosis and necrosis than those stimulated by exosomes released from non-irradiated cells. Non-irradiated PC3 cells co-incubated with exosomes from irradiated PC3 and DU145 cells exhibited more γH2AX foci than non-irradiated PC3 cells. Our results confirmed that DU145 cells are more radioresistant than PC3 cells and exosomes isolated from these cells may contribute to radiation resistance in prostate cancer. Thus, studying exosome functions, particularly in radiation resistance, is crucial for understanding carcinogenesis and optimizing radiotherapeutic methods.